STRATEGI GURU DALAM PENGELOLAAN KELAS YANG EFEKTIF UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA - Ginting, Rahmadani Fitri; Sari, Endang Puspa (Sindoro: Cendikia Pendidikan, 2024)
Strategies for effective classroom management include several aspects, such as arranging classroom layouts that support interaction, using technology as a learning medium, and using an individualized learning approach so that the needs of each student are met. This research uses a qualitative approach with descriptive methods. The data in this research are in the form of words and actions carried out by teachers. It is hoped that empirical findings can be described in more detail, clearer and more accurate, regarding teacher strategies in classroom management to increase student learning motivation. The research results showed that teachers need to develop appropriate strategies, such as good classroom settings, interactive learning approaches, and fair discipline, to encourage students' active involvement in the learning process. In addition, effective communication between teachers and students, as well as the use of technology and relevant teaching methods, also contribute to successful classroom management. With planned strategies and efficient implementation, teachers can facilitate a pleasant learning atmosphere, where students are motivated to participate actively, study harder, and achieve better results in academics.